THE EFFECT OF PELVIC ROCKING BIRTHBALL AND COLD COMPRESS ON LABOR PROGRESS AND LABOR PAIN IN THE ACTIVE PHASE OF THE FIRST STAGE - Husna Maulida; Eka Sutrisna; Arista Ardilla; Antika Sari; Merry Agustina (Getsempena Health Science Journal, 2026)
One of the causes of maternal death is prolonged labor, which is caused by abnormal uterine contractions that prolong labor time and labor pain, so that preventive efforts are needed, one of which is through pelvic rocking birthball therapy and cold compresses. Birthball is a physical therapy ball that helps the progress of labor, while cold compresses have an analgesic effect to reduce labor pain. The purpose of the study was the effect of Pelvic Rocking Birthball and Cold Compresses on labor progress and labor pain in the first stage of the active phase in TPMB, Lhoksukon District, North Aceh Regency. The research method was Quasy Experimental with a Posttest only control group design. The population of mothers giving birth in TPMB M, Lhoksukon District with a sample size of 50 samples consisting of 25 treatment groups and 25 control groups, consecutive sampling technique. The research instrument used a partograph for labor progress and a face scale (Wong-Baker face Pain Rating Scale), Data analysis used Independent Samples T-Test. The results showed that the administration of Pelvic Rocking Birthballs and cold compresses had an effect on labor progress (P-value 0.000) and labor pain (P-value 0.000). The average length of the first active phase of labor for respondents who used Pelvic Rocking Birthballs was 5 hours and 52 minutes (faster) compared to the non-treatment group. This proves that pelvic rocking birthballs and cold compresses are effective in increasing labor progress and reducing labor pain.